CHRONIC OBSTRUCTIVE PULMONARY DISEASE EXACERBATION - Radhitya, Ahmad Farizan; Zairus, Dedy (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive airway obstruction, irreversible and occurs concurrent chronic bronchitis, emphysema or both. The prevalence of COPD in the ratio between men and women is 3 to 1. Predisposing factors of reversible COPD should be sought and treated, which include smoking, hiperesponsif respiratory tract, respiratory tract infection, occupational exposure, pollution, genetic. Mr. M, 47 years old, present with shortness of breath, coughing and weight loss. Patients has history of consumption of anti-tuberculosis drugs, smoking for a quite long time, and also his mother has history of shortness of breath disease. Besides that, the physical examination found bronchial breath sound and wet ronchi additional sound by auscultation. Patients was diagnosed with COPD exacerbation and treated with oxygen therapy, bronchodilators, and antibiotics. COPD is a progressive, reversible and associated with an abnormal inflammatory response of the lungs to noxious particles or gases. [J Agromed Unila 2014; 1(1):49-54] Keywords: chronic obstructive, hiperesponsive, inflammatory, progressive, pulmonary disease